DESIGN UPPER STRUCTURE OF THE RIVER BAKI BRIDGE USES A STEEL FRAME - Tasliyatul Fuadiyah; Dedi Enda; Indriyani Puluhulawa (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2018)
In general, the bridge type is a reinforced concrete bridge, composite and steel frame. The Baki River Bridge was originally a 40 m long Wood type bridge connecting the village of Mengkopot - Tanjung Pisang because the condition of the Baki river bridge has been damaged especially on bridge floors and girders due to age, so it is planned to re-use the steel frame bridge structure. By using the steel bridge structure, it is expected that later it can be a comparison for the future bridge planning.In this study, the structure of the planned bridge consists of bridge slabs, sidewalk slabs, backrest pipes, longitudinal and transverse girders, steel frames, wind ties, and joints. By following the SNI T-02-2005 bridge loading standard, SNI T-03-2005 for planning steel bridge structures and SNI T-12-2004 for planning concrete structures on bridges.From the planning results obtained thickness 200 mm Bridge Slab and thick sidewalk slab 250 mm with a longitudinal girder profile used WF 600.200.11.17 mm steel with a distance between girders 1.75 m. Transverse girders of steel profiles WF 700,300.13.24 are used with the distance between girders 5 m. Used Steel profiles WF 400,400.13.21 as Main Frame and Steel WF profile 150.150.7.10 as profiles for wind ties.‘Keywords: Steel frame, girder, connection,